Material Culture of Natural History in Argentinean National Schools (1870-1900) - Mayoni, María Gabriela (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
Towards the end of the 19th century in Argentina, there was an exponential demand for didactic materials for the teaching of natural history as a result of its incorporation in the national schools. At the beginning a large number of collections and visual devices were acquired from abroad to equip cabinets, but there were also initiatives to create own collections with elements of local nature, creating incipient museums of natural history within the institutions. These artefacts reveal a material culture linked to scientific practices and the forms of study of nature promoted at the time. This article will analyze the circulation and integration of local knowledge in these teaching spaces settings, mostly circumscribed to regional context, as well as particular interests of some of its actors and their affinities with certain scientific practices and pedagogical ideas.